Exploring the Intersection of Islamic Values and Human Resource Management - Basalamah, Muhammad Syafii A (Advances in Human Resource Management Research, 2024)
The research investigates the integration of Islamic values into human resource management (HRM) practices, aiming to explore its implications for organizational dynamics and employee well-being. Employing a qualitative approach, the study conducts a comprehensive literature review to analyze existing scholarly works on the subject. The methodology involves systematic literature selection from academic databases, followed by data collection through thorough review and analysis of relevant literature. Thematic analysis is employed to identify recurring themes, patterns, and relationships within the literature. The findings highlight the significant influence of Islamic values on various HRM processes, including recruitment, training, performance appraisal, and conflict resolution. Islamic principles such as justice, equity, and compassion shape organizational culture, employee behavior, and organizational outcomes. The study also identifies theoretical frameworks like the Islamic Work Ethic (IWE) model and the Social Exchange Theory, offering valuable insights into the relationship between adherence to Islamic values and organizational outcomes. Moreover, empirical research underscores the importance of contextual factors and leadership practices in determining the effectiveness of integrating Islamic values into HRM. Overall, the study contributes to a deeper understanding of the intersection of Islamic values and HRM practices, providing insights for organizational leaders, policymakers, and scholars alike.